2015
DOI: 10.1016/j.nimb.2015.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Yield estimation of neutron-rich rare isotopes induced by 200 MeV/u 132 Sn beams by using GEANT4

Abstract: a b s t r a c tA so-called ''two-step reaction scheme'', in which neutron-rich rare isotopes obtained from ISOL are post-accelerated and bombarded on a second target, is employed to estimate the production yields of exotic rare isotopes. The production yields of neutron-rich rare isotope fragments induced by 200 MeV/u 132 Sn beams bombarded on a 9 Be target are estimated with Monte Carlo code, GEANT4. To substantiate the use of GEANT4 for this study, benchmark calculations are done for 80 MeV/u 59 Co, 95 MeV/u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In the absence of SCL1, the stable ion beams from the ECR ion sources or RIBs from the ISOL system are transported and accelerated by the injector system and the SCL3. Possible RIB generation and acceleration methods can be summarized as follows: [4].…”
Section: Overviewmentioning
confidence: 99%
“…In the absence of SCL1, the stable ion beams from the ECR ion sources or RIBs from the ISOL system are transported and accelerated by the injector system and the SCL3. Possible RIB generation and acceleration methods can be summarized as follows: [4].…”
Section: Overviewmentioning
confidence: 99%
“…It has been thoroughly tested and is being widely used in many different scientific fields, such as medical physics [32][33][34], accelerator-based radiation studies [35][36][37][38], neutron shielding studies [39][40][41], environmental radiation detection studies [42][43][44][45], etc. Additional information, validations and detailed descriptions of the GEANT4 can be found on the GEANT4 website [46].…”
Section: Simulation Toolsmentioning
confidence: 99%
“…Ultimately, RAON will attempt to use RIBs from the ISOL system to produce more neutron-rich ion beams by bombarding them to the IF target. The simulations have shown that the combination of ISOL and IF can produce new RIB species near the neutron dripline or enhance the yields of certain rare isotopes by large factors [5].…”
Section: Introductionmentioning
confidence: 99%